Left Ventricular Dimensions and Systolic Functıon in Beta Thalessemia - Balat, Ayse (Annals of Medical Research, 2021)
None
Keywords: s /b: ß-thalassemia, echocardiography, left ventricular systolic function, left ventricular dimensions